Antioxidants and Oral Health - GS, Shwetha; Mahajan, Harsh; Khare, Sumit; Hazari, Puja; Datla, Asmita; Yadav, Geetika (Journal of Orofacial Research, 2019)
The oral cavity is ubiquitous of various bacteria due to steady assaults of various food substances, soft drinks, alcohol, tobacco products etc. Antioxidants are substances that inhibit oxidation and prevent the formation of free radicals, which are responsible for cellular damage. Since the oral tissues are vulnerable to cellular damage caused by free radicals and oxidation process hence maintenance, a good level of antioxidants is very essential to achieve optimal oral health. This review highlights the role of antioxidants in the prevention of oral diseases.